Hakob Oshakan's Article "Hovhannes Tumanyan and His Creativity": а view 100 years later - Mnatsakanyan, Yeva (Bulletin of Yerevan University B: Philology, 2023)
The article presents the main provisions of H. Oshakan's voluminous article entitled  "Hovhannes Tumanyan and His Creativity», published in the August issue of the Boston magazine "Rodina" in 1923. They are the sum of the author's aesthetic and philosophical views on Tumanyan's creative work. Oshakan has been familiar with Tumanyan's works for a long time, and many years ago he expressed a controversial opinion about them, which varied from unconditional hostility to extremely high appreciation. The reason for such contradictory views of the Western Armenian critic on the Eastern Armenian literary and cultural values was his temperament, worldview, methodology, etc.In the studied article Oshakan, when analyzing Tumanyan's creative work, identifies the following thematic sections: "Lyric", "Epic", "Poet", "Storyteller", "Humeur". Our task is to reveal in the context of such a classification of works the aesthetic criteria of evaluation expressed by the critic, pointing out both the valuable observations of the author and completely unacceptable formulations. Comparative, comparative-historical and hermeneutic methods have been used during the study of the problem.Our article concludes that Hakob Oshakan, despite his unorthodox thinking and impressionistic preferences, highly valued Tumanyan and his creative world.
Keywords: H. Tumanyan; H. Oshakan; different aesthetic systems; epic colors; epic; psychology; storyteller; typology; method; "impressionist" critic